Pengembangan Karakter Berbasis Nilai Religius Di SMK Teknologi Komputer MBM Rawalo Banyumas - Sumiarti Sumiarti (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: This research is based on the researcher's interest to know more deeply and then to describe the implementation of character education in a high school / vocational school. As one of the SMK "suburbs", SMK Tekom MBM has a heavier task compared to the favorite SMA / SMK / MA because of the condition early students in vocational "suburbs" in lower quality, lower discipline, less good character. Although there are some students who already have a positive character, but the conditions in general are very different. They also come from underprivileged economic conditions. Schools "outskirts should certainly try harder to help learners get better change during their educational process. In the context of this research is how SMK Tekom MBM conducts character education by developing character values ​​as outlined by the Ministry of National Education but inspired by the teachings of Islam. This research produces findings of character development based on religious values ​​in SMK Tekom MBM implemented by: (1) integrated with subject learning process; (2) integrated in extracurricular activities; (3) integrated in the activities of intra-school organizations (OSIS); (4) Integrated in extra-school organizational activities, ie IPNU-IPPNU; (6) integrated in school culture. Keyword: karakter religius, pendidikan karakter, pendidikan karakter di sekolah, pendidikan karakter religius di SMK